Inline small‐angle X‐ray scattering‐coupled chromatography under extreme hydrostatic pressure. (17th November 2022) - Miller, Robert C.; Cummings, Cody; Huang, Qingqiu; Ando, Nozomi; Gillilan, Richard E.
Abstract: As continuing discoveries highlight the surprising abundance and resilience of deep ocean and subsurface microbial life, the effects of extreme hydrostatic pressure on biological structure and function have attracted renewed interest. Biological small‐angle X‐ray scattering (BioSAXS) is a widely used method of obtaining structural information from biomolecules in solution under a wide range of solution conditions. Due to its ability to reduce radiation damage, remove aggregates, and separate monodisperse components from complex mixtures, size‐exclusion chromatography‐coupled SAXS (SEC‐SAXS) is now the dominant form of BioSAXS at many synchrotron beamlines. While BioSAXS can currently be performed with some difficulty under pressure with non‐flowing samples, it has not been clear how, or even if, continuously flowing SEC‐SAXS, with its fragile media‐packed columns, might work in an extreme high‐pressure environment. Here we show, for the first time, that reproducible chromatographic separations coupled directly to high‐pressure BioSAXS can be achieved at pressures up to at least 100 MPa and that pressure‐induced changes in folding and oligomeric state and other properties can be observed. The apparatus described here functions at a range of temperatures (0°C–50°C), expanding opportunities for understanding biomolecular rules of life in deep ocean and subsurface environments.